Arf GTPase-activating proteins SMAP1 and AGFG2 regulate the size of Weibel-Palade bodies and exocytosis of von Willebrand factor - Asano Watanabe (The Company of Biologists, 2021)
Arf GTPase-Activating proteins (ArfGAPs) mediate the hydrolysis of GTP bound to ADP-ribosylation factors (Arfs), which are critical to form transport intermediates. ArfGAPs have been thought to be negative regulators of Arfs; however, accumulating evidence indicates that ArfGAPs are important for cargo sorting and promote membrane traffic. Weibel-Palade bodies (WPBs) are cigar-shaped secretory granules in endothelial cells that contain von Willebrand factor (vWF) as their main cargo. WPB biogenesis at the Golgi was reported to be regulated by Arf and their regulators, but the role of ArfGAPs has been unknown. In this study, we performed siRNA screening of ArfGAPs to investigate the role of ArfGAPs in the biogenesis of WPBs. We found two ArfGAPs, SMAP1 and AGFG2, to be involved in WPB size and vWF exocytosis, respectively. SMAP1 depletion resulted in small-sized WPBs, and the lysosomal inhibitor leupeptin recovered the size of WPBs. The results indicate that SMAP1 functions in preventing the degradation of cigar-shaped WPBs. On the other hand, AGFG2 downregulation resulted in the inhibition of vWF secretion upon Phorbol 12-myristate 13-acetate (PMA) or histamine stimulation, suggesting that AGFG2 plays a role in vWF exocytosis. Our study revealed unexpected roles of ArfGAPs in vWF transport.